Assessing The Current Indonesia’s Electricity Market Arrangements and The Opportunities to Reform - Setyawan, Dhani (Center of Biomass & Renewable Energy, Diponegoro University, 2014)
Existing subsidy arrangements and institutional settings in the Indonesian electricity sector distort investment decisions and lead to higher cost. Electricity supply is characterized by natural monopoly characteristics, requiring different management by governments than sectors with more straightforward market characteristics. Many countries have undergone significant re-structuring of their electricity sectors, away from one, state owned and vertically integrated monopoly supplier to a setting whereby competition has emerged either at the generation level and/or the retail level. Transmission and distribution networks are typically heavily regulated and transparent access arrangements are put in place as part of the restructuring efforts. The analysis showed that the current structure of Indonesia’s electricity sector firmly within Model 2 (the single buyer model) and highlights that Indonesia is currently towards the less-competitive end of the spectrum of Model 2, identifying significant potential for efficiency enhancing reforms within this structure. Constitutional limitations have hampered previous efforts to restructure the sector in Indonesia but there is significant room for incremental reform to improve incentives in the sector and reduce the cost of generation in the process.